(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Ulcerative colitis (UC) is a chronic disorder that involves inflammation. This study was carried out to examine the anti-inflammatory effect of the methanol extract of Brideliaferrugineastem barkinAcetic acid-induced ulcerative colitis inmaleWistarrats. Twenty-four rats were randomly divided into 6 groups of 4 animals each, colitis was thereafter induced by intrarectal administration of4% (v/v)Aceticacidin all except group 1, which received distilled water. For post-colitis induction treatment group 2 received distilled water, groups 3, 4 and 5 were orally administeredthe extract at doses of 100mg/kg, 200mg/kg and 400mg/kg, respectively while group 6 received sulfasalazine 500mg/kg orally.Post colitis induction, treatment lasted for 7 days and at the end of the experiment, colon samples were collected for estimation of antioxidant, inflammatory and histological parameters. Molecular docking study was also carried out to gain more insights about the promising anti-inflammatory compounds earlier identified in the extract.Results revealed that the extract significantly (p<0.05) attenuated the increased MDA, nitrite,TNF-α and IL-6 levels. Activities of SOD, CAT, MPO and GSH levelswere also, significantly (p<0.05) increased. Furthermore, molecular docking study revealed that α-amyrin may have contributed significantly to the anti-inflammatory activity of the extract because of its remarkable binding affinity for IL-6, iNOS, IL1-β,TNF-α and COX-2 relative to prednisolone and celecoxib. This study suggests that the extract attenuated acetic acid-induced colitis via antioxidative and anti-inflammatory mechanisms. .